Pengaruh Electronic Word Of Mouth, Brand Image, dan Product Knowledge Terhadap Purchase Intention - Gasik Arinalhaq (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
The purpose of this study is 1) to determine the effect of electronic word of mouth on purchase intention, 2) to determine the effect of brand image on purchase intention, 3) to determine the effect of product knowledge on purchase intention, 4) to determine the effect of electronic word of mouth, brand image, and product knowledge together on purchase intention. The research method used in this study is the associative method. Data collection techniques using questionnaires. While the data analysis methods used are classical assumption tests, multiple regression analysis, t-tests, F-tests, and Determination Coefficient Analysis. The results of this study are 1) From partial testing using the t-test, the sig value = 0.001 <0.05 is obtained so that it can be concluded that there is a significant effect of electronic word of mouth on purchase intention. 2) From partial testing using the t-test, the sig value = 0.015 <0.05 is obtained so that it can be concluded that there is a significant effect of brand image on purchase intention. 3). From partial testing using the t-test, the sig value = 0.084 ? 0.05 is obtained, so it can be concluded that there is an insignificant effect of product knowledge on purchase intention. 4). From simultaneous testing, the sig value = 0.000 <0.05 is obtained, so it can be concluded that there is a significant effect of electronic word of mouth, brand image, and product knowledge together on purchase intention.